Nepal’s Water Resources: Blessing or Curse ? - Shrestha, Rabindra Bahadur (Hydro Nepal: Journal of Water, Energy and Environment, 2016)
For half a century, Nepal has been chanting the ‘Mantra’ of 83,000 MW hydropower potential. When Nepal was in its childhood as a young democratic nation in the 1950s, India, with its vast ‘experience’ under the British colonial rule (colonial mindset), extracted lop-sided agreements on the Koshi, Gandaki and Mahakali rivers. Whereas India irrigates 12,200,000 acres of land, flood mitigates flood hazards and benefits from other intangible benefits. Nepal gets a meager 160,000 acres irrigation facility (1.3 percent of total irrigation benefits) from these unequivocal biased agreements. The adverse social and ecological impacts in Nepal are unaccounted for. Such water resource agreements have resulted in the sad present-day plight of Nepal: social life and industries are in total disarray with dismally low economic growth rates (GDP) forcing millions of Nepalese to seek employment abroad. Before it gets out of hand, India’s direct/indirect domination over Nepal’s water resources and politics should end, so that Nepal can develop its economy and hydropower in peace. Nepal should first develop run-of-river projects as per the modality of 456 MW Upper Tamakoshi Hydroelectric Project (cost 1000 US$/kWh) and medium size storage hydropower projects (140 MW Tanahu). Muddling with large storage projects like 1200 MW Budhi Gandaki HEP will only further delay the execution of RoR projects. NEA’s technical capability should be improved to build and oversee hydropower projects and INPS. HYDRO Nepal Journal Journal of Water, Energy and Environment Issue: 19 Page: 11- 15